SISTEM KINERJA DAN KEPEGAWAIAN MENGGUNAKAN MULTI FACTOR EVALUATION PROCESS (STUDI KASUS: SMK MA'ARIF 1 TEMON YOGYAKARTA) - Agus Sidiq Purnomo; Anief Fauzan Rozi; Dina Yulina Heriyani (LPPM Universitas Abdurrab, 2026)
A personnel information system is an important requirement for educational institutions in managing employee data digitally. SMK Ma'arif 1 Temon Yogyakarta currently does not have an integrated personnel information system (SIMPEG), so the process of recruitment, attendance, employee profiles, leave applications, career paths, and performance appraisal are still done manually. This study aims to produce a prototype of a personnel information system and to apply the Multi Factor Evaluation Process (MFEP) method for employee performance assessment. The system development method uses the Waterfall Model with assessment criteria including years of service, education level, position, rank, and additional duties. The results showed that the system was able to perform MFEP calculations properly, producing the highest ranking for Alternative A22 with a score of 4.30. System functionality testing shows all features run well. This prototype can be a solution for digitalization of personnel management at SMK Ma'arif 1 Temon.